2004
DOI: 10.1158/0008-5472.can-03-1941
|View full text |Cite
|
Sign up to set email alerts
|

A Fragment of Histidine-Rich Glycoprotein Is a Potent Inhibitor of Tumor Vascularization

Abstract: In this study, we show that recombinant human histidine-rich glycoprotein (HRGP) has potent antiangiogenic properties as judged from effects on a syngeneic tumor model in C57/bl6 mice. Growth of fibrosarcoma, a very aggressive tumor, was reduced by >60% by HRGP treatment, and tumor angiogenesis was dramatically decreased. Treatment with HRGP led to increased apoptosis and reduced proliferation in the tumors. In contrast, HRGP did not affect apoptosis or DNA synthesis in endothelial cells or tumor cells in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 49 publications
6
135
2
Order By: Relevance
“…Similar to PF4, the His/Pro-rich domain of HRG is capable of binding to heparan sulfate on the endothelial cell surface (27) and to interfere with VEGF-induced signaling and angiogenesis (24). However, the inhibition exerted by HRG is not due to a direct competition between HRG and the growth factor for access to heparan sulfate (18,24), as in the case of PF4. Instead, HRG targets focal adhesion function in endothelial cells and thereby prevents an angiogenic response to VEGF (38).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to PF4, the His/Pro-rich domain of HRG is capable of binding to heparan sulfate on the endothelial cell surface (27) and to interfere with VEGF-induced signaling and angiogenesis (24). However, the inhibition exerted by HRG is not due to a direct competition between HRG and the growth factor for access to heparan sulfate (18,24), as in the case of PF4. Instead, HRG targets focal adhesion function in endothelial cells and thereby prevents an angiogenic response to VEGF (38).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we identified a proteolytically released 30-kDa fragment, derived from the His/Prorich domain of HRG, as mediator of its antiangiogenic effect (18). The fragment must be released from the full-length protein to be active and can be found in purified fractions of HRG in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations